Using meta-ethnography to synthesize relevant studies: capturing the bigger picture in dementia with challenging behavior within families - Feast, Alexandra; Orrell, Martin; Charlesworth, Georgina; Poland, Fiona; Featherstone, Katie; Melunsky, Nina; Moniz-Cook, Esme (SAGE, 2018)
In understanding the range and depth of people’s experiences, it is important to include the wide range of approaches which capture the richness within a given knowledge base. However, systematic reviews using quantitative data alone risk missing findings that can contribute to a better understanding of a research question. In response, meta-ethnography has emerged as a potentially useful method to synthesize and integrate both qualitative and quantitative data from different perspectives using qualitative methodology. In this case study, we describe how we have used meta-ethnography to better understand how families experience dementia. We address a particular issue of selecting the highest quality evidence across a range of epistemologies.